Structural, morphological and optical properties of ZnO thin films grown by time-dependent chemical bath deposition - Alphonse Déssoudji Gboglo; Mazabalo Baneto; Ognanmi Ako; Komlan Segbéya Gadedjisso-Tossou; Bruno Grandidier; Muthiah Haris; Muthuswamy Senthilkumar; Kekeli N’Konou (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study investigates the effect of deposition time on the structural, morphological, and optical properties of ZnO thin films synthesized by single-step chemical bath deposition (CBD) without the use of a seed layer. The films were systematically characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and UV-Visible spectroscopy in order to establish correlations between growth conditions and film properties. XRD analysis confirmed that all synthesized films are polycrystalline and crystallize in the hexagonal wurtzite structure, with average lattice parameters of a = 3.247 Å and c = 5.209 Å. The crystallite size increased slightly from 13.27 nm to 14.05 nm with increasing deposition time, indicating improved structural ordering and crystallinity. FTIR spectra verified the presence of characteristic Zn–O vibrational modes together with surface hydroxyl groups and other functional bonds related to the growth process. SEM images revealed a strong dependence of surface morphology on deposition time: ZnO microrods evolved from loosely distributed to more compact and densely packed assemblies as the deposition progressed, confirming enhanced film coverage. Optical measurements highlighted significant modifications in the transparency and band structure of the films. The average optical transmittance in the visible range decreased progressively from 68% to 52% when deposition time was extended from 30 to 120 minutes, reflecting increased film density. Concurrently, the optical band gap narrowed from 3.27 eV to 3.22 eV. These findings demonstrate that single-step CBD provides a reliable and controllable route for synthesizing ZnO thin films with tunable physical properties.